A long goodbye to Bismarck? : the politics of welfare reforms in continental Europe / Bruno Palier (ed.). - Palier, Bruno (Changing welfare states, 2010)
A Long Goodbye to Bismarck? is the first study to provide an exhaustive comparative account of all welfare reforms in continental Europe during the past three decades, covering Austria, Belgium, the Czech Republic, France, Germany, Hungary, Italy, the Netherlands, Poland, Slovakia, Spain, and Switzerland.